S14 Time Trends And Risk Factors For Hospitalisation After Community-acquired Pneumonia In Older Adults In England. (10th November 2014) - Millett, ERC; De Stavola, BL; Quint, JK; Smeeth, L; Thomas, SL
Abstract : Introduction and objectives: Hospitalisation rates for community-acquired pneumonia (CAP) among older individuals have increased in Europe, but the reasons for this remain unclear. It may be due to increasing incidence of CAP in older adults, or an increasing tendency to hospitalise – either due to worsening co-morbidities, and/or changes in service provision. We used English linked electronic health records to investigate trends in hospitalisation after a CAP diagnosis independent of CAP incidence, and determinants of any increasing trend. Methods: General practice records from the Clinical Practice Research Datalink (1998–2011) were linked to hospital admission records and mortality data, and CAP episodes among patients aged ≥65 years were identified. Episodes resulting in hospitalisation within 28 days of CAP diagnosis were compared to non-hospitalised CAP episodes, and multilevel logistic regression models built to estimate odds ratios for co-morbidities, frailty, and other factors, and to predict the probability of hospitalisation over time. Indicators of CAP severity (including mortality in the 28 days post-CAP) and pathways of care were also examined as explanations for hospitalisation trends. Results: Hospitalisation after CAP increased markedly over the time period; after controlling for a wide range of comorbidities and other factors, the predicted probability of hospitalisation rose from 57% (1998–2000) to 86% (2009–2010). Factors associated with hospitalisation included 14 co-morbidities, five frailty factors, and four medications/vaccinations. In the fully adjusted model most of these factors were associated with increased odds of hospitalisation, but some (including dementia and terminal illness) lowered the odds of hospitalisation. Over the study period, a growing proportion of CAP patients were admitted to hospital via A and E and the proportion referred by general practitioners decreased. 28-day mortality decreased over time. Conclusions: Hospitalisation after CAP among those aged ≥65 years has increased in England, independent of co-morbidity and frailty factors, while mortality has decreased. Changes in service provision, patient and physician behaviours may play a role in increasing CAP hospitalisations. If the incidence of CAP in this age group also continues to increase, these combined trends will place an expanding burden on the health service.